The Masculine Cross : A History of Ancient and Modern Crosses and Their Connection with the Mysteries of Sex Worship; Also an Account of the Kindred Phases of Phallic Faiths and Practices - Anonymous (Salt Lake City, UT : Project Gutenberg, 2012)
"The Masculine Cross" by Anonymous is a historical account written in the early 20th century. This work delves into the origins and significance of the cross as a symbol throughout various cultures and time periods, exploring its connections to ancient and modern practices of sex worship and phallic faiths. The text argues against the common belief that the cross is of solely Christian origin, prompting readers to reconsider the symbol$1 (Bs extensive and complex history across different civilizations. The opening of the text sets the stage for a broad historical exploration of the cross, asserting its universal presence across cultures and time periods long before its association with Christianity. It challenges the notion that the cross originated with the crucifixion of Christ, instead linking it to ancient pagan traditions, particularly in Egypt and India, where it was revered as a religious symbol. The author introduces various forms of the cross found in antiquity, such as those present in Assyrian, Egyptian, and Indian monuments, highlighting the symbol$1 (Bs multifaceted meanings and its role in rituals associated with fertility and creation, thereby establishing a foundation for the subsequent chapters that promise further examination of the cross's significance within broader philosophical and religious contexts. (This is an automatically generated summary.)s
Release date is 2012-04-10
E-text prepared by the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Phallicism; Crosses